Preference for Sago and nutrient intake among communities consuming Sago in Kepulauan Meranti District, Riau Province, Indonesia - Syartiwidya, Syartiwidya; Martianto, Drajat; Sulaeman, Ahmad; Tanziha, Ikeu; Rimbawan, Rimbawan (Jurnal Gizi dan Pangan, 2019)
This study aimed to analyse the preference for sago products and nutritional intake of the community consuming sago in Kepulauan Meranti District, Riau Province. A cross-sectional study was conducted and 181 adults was purposively selected subjects in Tebing Tinggi Timur Sub-district, Kepulauan Meranti District, Riau Province. The data obtained were subject characteristics, anthropometry, preferences for sago products, and nutritional intake from semi-quatitative food frequency questionnaire and food recall. The most preferred sago products out of 10 types of processed sago products were sago noodles (89.9%), sago lempeng (86.9%), and lemak sago (85.4%). Sago consumption frequencies among the subjects were mostly ‘often’ (39.2%) and ‘quite often’ (30.6%). The average amount of sago consumption was 173.7±88.3 g/day. The subject's average daily energy intake was 1864±468 kcal and the average protein intake was 48.4±21.7 g. The energy adequacy levels of subjects who consumed sago <140 g/day and ≥140 g/day were categorized as ‘normal’ (25.9% and 34.0% respectively). Meanwhile, the average level of protein adequacy were categorized as deficit (38.3% and 43.0% respectively). The carbohydrate adequacy levels were categorized as ‘excessive’ (80.2% and 71.0% respectively). The fat adequacy levels were categorized as ‘excessive’ (90.1% and 92.0% respectively). Sago noodles and lemak sago are two potential sago products to be developed as alternative carbohydrate sources due to their high frequency and preferability.